Tantangan dalam Eksekusi Putusan Arbitrase Internasional Studi Kasus Churchill Mining PLC Vs Pemerintah Republik Indonesia - Catur Aji Pamungkas; Hesti Septianita (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
This study explores the challenges in executing international arbitration awards through the analysis of the case involving Churchill Mining Plc, Planet Mining Pty Ltd, and the Government of the Republic of Indonesia. Intensive business interactions often result in disputes that require resolution through international arbitration. The execution process is hindered by requests for annulment of awards, prolonging legal uncertainty and harming both parties. A holistic research method is employed, combining empirical legal analysis and case studies. Data from official documents, arbitration awards, and legal literature are analyzed to identify factors influencing the implementation of arbitration awards. Findings highlight the need to enhance efficiency in international investment dispute resolution, by expediting the annulment process and implementing awarded decisions promptly. This is crucial to support sustainable economic growth and bolster investor confidence in a country's legal system. The study provides deeper insights into practical challenges in the execution of international arbitration awards and lays the groundwork for relevant policy recommendations.